Use of MALDI-TOF Mass Spectrometry for the Fast Identification of Gram-Positive Fish Pathogens - Assis, Gabriella B. N.; Pereira, Felipe L.; Zegarra, Alexandra U.; Tavares, Guilherme C.; Leal, Carlos A.; Figueiredo, Henrique C. P. (Frontiers in Microbiology, 2017)
Gram-positive cocci, such as Streptococcus agalactiae, Lactococcus garvieae, Streptococcus iniae, and Streptococcus dysgalactiae subsp. dysgalactiae, are found throughout the world, particularly in outbreaks in farmed fish, and are thus associated with high economic losses, especially in the cultivation of Nile Tilapia. The aim of this study was to evaluate the efficacy of matrix-assisted laser desorption ionization (MALDI)-time of flight (TOF) mass spectrometry (MS) as an alternative for the diagnosis of these pathogens. One hundred and thirty-one isolates from Brazilian outbreaks assisted by the national authority were identified using a MALDI Biotyper from Bruker Daltonics. The results showed an agreement with respect to identification (Kappa=1) between this technique and 16S ribosomal RNA gene sequencing for S. agalactiae and L. garvieae. However, for S. iniae and S. dysgalactiae subsp. dysgalactiae, perfect agreement was only achieved after the creation of a custom main spectra profile, as well as further comparisons with 16S ribosomal RNA and multilocus sequence analysis. MALDI-TOF MS was shown to be an efficient technology for the identification of these Gram-positive pathogens, yielding a quick and precise diagnosis.